Membrane and synaptic defects leading to neurodegeneration in Adar mutant Drosophila are rescued by increased autophagy. - Khan, A.; Paro, S.; McGurk, L.; Sambrani, N.; Hogg, M.C.; Brindle, J.; Pennetta, G.; Keegan, L.P.; O'Connell, M.A. (BMC Biology, 2020)
In fly brains, the Drosophila Adar (adenosine deaminase acting on RNA) enzyme edits hundreds of transcripts to generate edited isoforms of encoded proteins. Nearly all editing events are absent or less efficient in larvae but increase at metamorphosis; the larger number and higher levels of editing suggest editing is most required when the brain is most complex. This idea is consistent with the fact that Adar mutations affect the adult brain most dramatically. However, it is unknown whether Drosophila Adar RNA editing events mediate some coherent physiological effect. To address this question, we performed a genetic screen for suppressors of Adar mutant defects. Adar5G1 null mutant flies are partially viable, severely locomotion defective, aberrantly accumulate axonal neurotransmitter pre-synaptic vesicles and associated proteins, and develop an age-dependent vacuolar brain neurodegeneration. A genetic screen revealed suppression of all Adar5G1 mutant phenotypes tested by reduced dosage of the Tor gene, which encodes a pro-growth kinase that increases translation and reduces autophagy in well-fed conditions. Suppression of Adar5G1 phenotypes by reduced Tor is due to increased autophagy; overexpression of Atg5, which increases canonical autophagy initiation, reduces aberrant accumulation of synaptic vesicle proteins and suppresses all Adar mutant phenotypes tested. Endosomal microautophagy (eMI) is another Tor-inhibited autophagy pathway involved in synaptic homeostasis in Drosophila. Increased expression of the key eMI protein Hsc70-4 also reduces aberrant accumulation of synaptic vesicle proteins and suppresses all Adar5G1 mutant phenotypes tested. These findings link Drosophila Adar mutant synaptic and neurotransmission defects to more general cellular defects in autophagy; presumably, edited isoforms of CNS proteins are required for optimum synaptic response capabilities in the brain during the behaviorally complex adult life stage.